Загрузил alex_shilina74

Решение уравнений

Реклама
Решение уравнений
Решение уравнений
Решение уравнений
Решение уравнений
1) 4y + 7 = 5y + 4
2) 35 – 11m = 3m + 21
3) 10 – 9y = 70 – 6y
4) -9x – 56 = 5x
3) 4y + 7 = 5y + 4
4) 35 – 11m = 3m + 21
3) 10 – 9y = 70 – 6y
4) -9x – 56 = 5x
5) 4y + 7 = 5y + 4
6) 35 – 11m = 3m + 21
3) 10 – 9y = 70 – 6y
4) -9x – 56 = 5x
7) 4y + 7 = 5y + 4
8) 35 – 11m = 3m + 21
3) 10 – 9y = 70 – 6y
4) -9x – 56 = 5x
5) 56 – 9n = -5n
6) 15 – 8x = 2 – 9x
7) 10z + 7 = 9z + 5
8) 17 – 8y = 4y – 7
5) 56 – 9n = -5n
6) 15 – 8x = 2 – 9x
7) 10z + 7 = 9z + 5
8) 17 – 8y = 4y – 7
5) 56 – 9n = -5n
6) 15 – 8x = 2 – 9x
7) 10z + 7 = 9z + 5
8) 17 – 8y = 4y – 7
5) 56 – 9n = -5n
6) 15 – 8x = 2 – 9x
7) 10z + 7 = 9z + 5
8) 17 – 8y = 4y – 7
9) 10 – 11n = 15 – 12n
10) -9z +32 = 7z
11) 25 – 12m = 45 – 8m
12) 5y + 15 = 4y + 20
9) 10 – 11n = 15 – 12n
10) -9z +32 = 7z
11) 25 – 12m = 45 – 8m
12) 5y + 15 = 4y + 20
9) 10 – 11n = 15 – 12n
10) -9z +32 = 7z
11) 25 – 12m = 45 – 8m
12) 5y + 15 = 4y + 20
9) 10 – 11n = 15 – 12n
10) -9z +32 = 7z
11) 25 – 12m = 45 – 8m
12) 5y + 15 = 4y + 20
13) -7x – 40 = 3x
14) 10n – 9 = 7n +12
15) 14 = 2y – 2
16) -10z + 75 = -5z
13) -7x – 40 = 3x
14) 10n – 9 = 7n +12
15) 14 = 2y – 2
16) -10z + 75 = -5z
13) -7x – 40 = 3x
14) 10n – 9 = 7n +12
15) 14 = 2y – 2
16) -10z + 75 = -5z
13) -7x – 40 = 3x
14) 10n – 9 = 7n +12
15) 14 = 2y – 2
16) -10z + 75 = -5z
17) 15 + 4y = y
18) 24 – 15m = 15 – 14m
19) 6x + 5 = 7x +3
20) 28 = 7n – 7
17) 15 + 4y = y
18) 24 – 15m = 15 – 14m
19) 6x + 5 = 7x +3
20) 28 = 7n – 7
17) 15 + 4y = y
18) 24 – 15m = 15 – 14m
19) 6x + 5 = 7x +3
20) 28 = 7n – 7
17) 15 + 4y = y
18) 24 – 15m = 15 – 14m
19) 6x + 5 = 7x +3
20) 28 = 7n – 7
21) 17 – 12n = 3n – 13
22) 8y – 15 = 7y – 12
23) 11m – 13 = 15 – 3m
24) 30 – 15z = 40 – 14z
21) 17 – 12n = 3n – 13
22) 8y – 15 = 7y – 12
23) 11m – 13 = 15 – 3m
24) 30 – 15z = 40 – 14z
21) 17 – 12n = 3n – 13
22) 8y – 15 = 7y – 12
23) 11m – 13 = 15 – 3m
24) 30 – 15z = 40 – 14z
21) 17 – 12n = 3n – 13
22) 8y – 15 = 7y – 12
23) 11m – 13 = 15 – 3m
24) 30 – 15z = 40 – 14z
25)
26)
27)
28)
𝑥−1
2
2𝑥−3
3
𝑥+3
2
𝑥−7
3
=
4+5𝑥
3
= −5
=
3𝑥−2
7
= −2
25)
26)
27)
28)
𝑥−1
2
2𝑥−3
3
𝑥+3
2
𝑥−7
3
=
4+5𝑥
3
= −5
=
3𝑥−2
7
= −2
25)
26)
27)
28)
𝑥−1
2
2𝑥−3
3
𝑥+3
2
𝑥−7
3
=
4+5𝑥
3
= −5
=
3𝑥−2
7
= −2
25)
26)
27)
28)
𝑥−1
2
2𝑥−3
3
𝑥+3
2
𝑥−7
3
=
4+5𝑥
3
= −5
=
3𝑥−2
7
= −2
Скачать